QUALITY OF HEALTH SERVICES AT SIEMPAT RUBE COMMUNITY HEALTH CENTER, PAK-PAK BHARAT DISTRICT - Natalia Padang; Muklir; Sufi; Ti Aisyah; Ferizaldi (RADJA PUBLIKA, 2025)
Quality of Health Services at Siempat Rube Health Center, Siempat Rube District, Pakpak Bharat Regency, Poor service will greatly affect patient assessment of health center services, The formulation of the problem of this study is how is the quality of health services at the Siempat Rube Health Center and the inhibiting factors in Health Services at the Siempat Rube Health Center, Pakpak Bharat Regency. This study uses a descriptive qualitative approach, namely observation, interviews, and documentation as data collection techniques, then data analysis techniques, namely data reduction, data presentation, drawing conclusions/verification. The results of the study indicate that the quality of health services at the Siempat Rube Health Center, Pakpak Bharat Regency, seen from the aspect of Physical Evidence (Tangibles) of inadequate and unsatisfactory facilities and infrastructure. Responsiveness in the service process is good, assessed from the alertness and responsiveness in serving patients. Assurance (Annsurence) lack of medical personnel. Empathy (Empathy) is good, assessed from the attitude of employees who are friendly and accept criticism and suggestions from the community. The obstacles are poor road access infrastructure to the health center, lack of medical personnel such as medical records and dental nurses, health center employees who are less disciplined and professional in working. The hope is for the Siempat Rube Pakpak Bharat Health Center to complete the facilities that are not yet available and medical personnel